The Influence of Emotional Counseling on Self-Acceptance of Chronic Illness Patients in the Terminal Phase - Hoda, Ferdinandus Suban; Zaenal, Zaenal; Hastutiningtyas, Wahidyanti Rahayu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Patients with terminally ill chronic illnesses often experience difficulty accepting their condition, which impacts their quality of life. One intervention that can be used is emotional counseling, which aims to help patients understand and manage negative emotions, thereby increasing self-acceptance. This study aims to determine the effect of emotional counseling on self-acceptance in terminally ill chronic patients. The research method used a quasi-experimental design with a pretest-posttest approach. control group Design. A sample of 40 respondents was divided into an intervention group (20 patients received emotional counseling) and a control group (20 patients received standard care). The research instrument was a validated self-acceptance scale questionnaire. The results showed a significant increase in self-acceptance in the intervention group compared to the control group (p < 0.05). In conclusion, emotional counseling has a positive effect on increasing self-acceptance in patients with chronic illnesses in the terminal phase. Suggestions: Emotional counseling can be part of palliative nursing interventions in hospitals.